The year I flew away - Arnold, Marie (Versify, Houghton Mifflin Harcourt, 2021)
After moving from her home in Haiti to her uncle's home in Brooklyn, ten-year-old Gabrielle, feeling bullied and out of place, makes a misguided deal with a witch.